VIEWS OF YOUNG PEOPLE ON THE IMPORTANCE OF MARKETING COMMUNICATION IN TERMS OF ACCESSING EUROPEAN FUNDS - ORZAN, Mihai; RADU, Anamaria Cătălina; DOBRESCU, Andra Iuliana; MITRICĂ, Maria Cristina (Annales Universitatis Apulensis Series Oeconomica, 2015)
With Romania’s accession to the European Union, it has benefited from a number of advantages including the possibility of accessing funds. Projects financed from external funds are some of the most important instruments that are aimed at the improvement of businesses conducted in the country. In recent years, Romania has registered fairly low values in terms of the absorption of European funds. Excessive bureaucracy and how the communication process takes place have put a powerful imprint on the activities undertaken in this field. The study presented in this paper aims to identify young people’s views on the importance of marketing communication in this business sector. To meet the objectives, a quantitative research was conducted on a sample of 70 respondents. The data were analyzed using the IBM SPSS Statistics 20 software.